Characterization and optimization of extracellular L-Asparaginase production by selected Actinomycete strain isolated from an algerian wheat bran - Chergui, Achour; Kecha, Mouloud; Tighrine, Abderrahmane; Adrar, Nabil; Bouzida, Samira; Titouche, Yacine; Boughani, Lhadi; Kadri, Nabil; Houali, Karim (Cellular and Molecular Biology, 2018)
L-Asparaginase is an enzyme that hydrolyses the amino acid L-Asparagine into aspartic acid and ammonia. As a medication, L-Asparaginase is used in chemotherapy to treat acute lymphoblastic leukaemia by depleting circulating Asparagine and depriving tumor cells. Interest in Actinomycetes as potential producers of antibiotics and enzymes encouraged us to investigate an isolated strain (CA01) from soft wheat bran.The Actinomycete strain was characterized based on its morphological and biochemical characteristics and selected due to a proved promising ability to produce L-Asparaginase optimized in both solid and liquid media cultures.The conditions of enzyme production were standardized according to a one-factor-at-a-time (OFAT) experimental design.To obtain optimal medium combination, a Box-Behnken Response Surface Methodology (RSM) has been adopted by choosing the most influential factors. The optimal conditions for the enzyme production were (g/l): L-Asparagine 10.7; Glucose 2.7; starch 7, in based medium containing (g/l): K2HPO4 0.5; MgSO4, 7H2O 0.1, corresponding to an optimal enzymatic activity of 8.03 IU/ml at 27.83°C. The maximum production of enzyme was reached on the sixth day of experiment. The ANOVA test (P value Ë‚ 0.05) and adjusted R2 values close to the experimental R2 show that the obtained model of the active L-Asparaginase of CA01 strain production is significant with the following linear terms: temperature, substrate concentration, Glucose concentration and there squared.